Kinase Signaling in Dendritic Development and Disease - Nourbakhsh, Kimya; Yadav, Smita (Frontiers in Cellular Neuroscience, 2021)
Dendrites undergo extensive growth and remodeling during their lifetime. Specification of neurites into dendrites is followed by their arborization, maturation, and functional integration into synaptic networks. Each of these distinct developmental processes is spatially and temporally controlled in an exquisite fashion. Protein kinases through their highly specific substrate phosphorylation regulate dendritic growth and plasticity. Perturbation of kinase function results in aberrant dendritic growth and synaptic function. Not surprisingly, kinase dysfunction is strongly associated with neurodevelopmental and psychiatric disorders. Herein, we review, (a) key kinase pathways that regulate dendrite structure, function and plasticity, (b) how aberrant kinase signaling contributes to dendritic dysfunction in neurological disorders and (c) application of emergent technologies that can be applied to dissect the role of protein kinases in dendritic structure and function.